Kunci identifikasi lalat buah (Diptera: Tephritidae) di Kabupaten Bogor dan sekitarnya - Anik Larasati; Purnama Hidayat; Damayanti Buchori (Perhimpunan Entomologi Indonesia, 2016)
Identification key was developed for 18 species of fruit flies (Bactocera spp.) found in Bogor district. Morphological characters were used as background information for key development: 2 genus and 4 subgenus were identified in the process. Fruit fly species in this identification was Bactrocera (Bactrocera) albistrigata de meijere, Bactrocera (Bactrocera) carambolae Drew & Hancock, Bactrocera (Bactrocera) caudata Fabricus, Bactrocera (Bactrocera) latifrons White & Liquido, Bactrocera (Bactrocera) limbifera Bezzi, Bactrocera (Bactrocera) melastomatos Drew & Hancock, Bactrocera (Bactrocera) moluccensis Perkins, Bactrocera (Bactrocera) occipitalis Drew & Hancock, Bactrocera (Bactrocera) papayae Drew & Hancock, Bactrocera (Bactrocera) tau Walker, Bactrocera (Bactrocera) umbrosa Fabricius, Bactrocera (Bactrocera) usitata Drew & Hancock, Bactrocera (Bactrocera) verbascifoliae Drew & Hancock, Bactrocera (Bactrocera) vulta Hardy, Bactrocera (Bulladacus) mcgregori Bezzi, Bactrocera (Zeugodacus) calumniata Hardy, Bactrocera (Bactrocera) cucurbitae Coquillet, Dacus (Callantra) longicornis Wiedemann. Preparation of identification keys were done by created a matrix of characters, through comparing several characters such as face spot, lateral postsutural vittae, the color of the legs, wide and narrow costal band, medial longitudinal band, as well as the lateral margin of terga III to V.